44.5k views
2 votes
Multiply:
i) (ax + b) by (cx + d)

2 Answers

5 votes

Answer:

  • i) acx² + adx + bcx + bd

Step-by-step explanation:

Hello!

i) Multiply (ax + b) by (cx + d)

(ax + b)(cx + d) =

= axcx + adx + bcx + bd =

= acx² + adx + bcx + bd

Success! ☺️

User Noortheen Raja
by
5.3k points
3 votes

Answer:

acx² + adx + bcx + bd

Explanation:

(ax + b)(cx + d)

Each term in the second factor is multiplied by each term in the first factor

ax(cx + d) + b(cx + d) ← distribute parenthesis

= acx² + adx + bcx + bd

User Djolf
by
5.0k points